Analisis Pengaruh Kinerja Keuangan terhadap Return Saham Studi Kasus pada Industri Manufaktur yang Terdaftar di Bursa Efek Indonesia - Sirajuddin; Muh Rusli; Andi Syamsul Rijal (Journal of Institution and Sharia Finance, 2024)
The aim of this research is to analyze the influence of financial performance on stock returns in manufacturing industries listed on the Indonesia Stock Exchange.The analytical method used in this research is a quantitative descriptive approach. With a population of all manufacturing industries registered on the Indonesian stock exchange using porpusive sampling. The results of this research show that based on the results of data analysis and discussion in the previous chapter, this research resulted in the following conclusions; Most manufacturing industries listed on the Indonesian Stock Exchange produce negative EVA. This indicates that the industry does not create added economic value because the company does not take into account the cost of capital for the invested equity. ROA, ROE, and EVA do not have a significant effect on stock returns in the manufacturing industry listed on the Indonesia Stock Exchange. This happens because it turns out that company profits are one of the indicators for calculating ROA, ROE and EVA are not the only indicators in making stock price decisions. The cost of capital, which is a component of EVA calculations, is greatly influenced by interest rates. Apart from that, there are differences in technical calculations, company size, conditions of the Indonesian money market, the existence of internal factors other than economic fundamentals, interest rates, devaluation, economic growth, government spending and money supply, sales, sales growth, costs, cash dividends, social, political and economic conditions are factors that must be considered in determining stock returns.